Ranking of human factors affecting contractors’ risk attitudes in the Malaysian construction industry - Moshood, Taofeeq.D.; Adeleke, A. Q.; Nawanir, Gusman; Fatimah, Mahmud (Elsevier, 2020)
Project risk assessment is an operative tool for development and controlling cost, time, and attaining the technical performance of a construction project. Construction projects often face a lot of uncertainties, which place building and road construction projects at the risk of time overruns, cost as well as poor quality delivery. Therefore, project risk management is an essential part of the decision-making process in a construction company as it determines the success or failure of construction projects. This paper aims to determine the extent of construction risk management among the Malaysian construction companies and to rank the specific factors affecting contractors’ risk attitudes among the Malaysian construction companies. Simple random under probability sampling techniques were used. A review of relevant literature and a questionnaire with a five-point Likert scale of (1) very low to (5) very high was adopted in gathering data regarding the extent of risk management and ranking of human factors affecting contractors’ risk attitudes in the Malaysian construction companies. The sample size used for analysis is 146. This study also focused on the G7 contractors operating in the Malaysian construction industry. Findings revealed that construction risk management has not been highly implemented among the Malaysian construction companies and that the five leading factors affecting risk attitudes of contractors are as follows: work experience, physical health, educational background, professional competence, and emotional intelligence. The outcomes of this study can be used to inform decision-makers about strategies for risk management in handling contractors’ risk attitudes, thus providing stakeholders with the necessary information for enhancing risk management performance in the construction industry.